Noradrenergic hypothesis of neurodegeneration and astroglia - Zorec, Robert (Henry Stewart Talks, 2024)
Dementia and neurodegeneration, Noradrenergic system in thinking, Lead hypotheses for understanding AD, Astrocytes in neurodegeneration, Adrenergic control of astrocytes (morphology, vesicles, metabolism), TDP-43 containing astrocytes accumulate lipid droplets